Sternocostoclavicular Hyperostosis: An Insufficiently Recognized Clinical Entity. Issue 10 (4th April 2017) - Sugase, Taro; Akimoto, Tetsu; Kanazawa, Hidenori; Kotoda, Atsushi; Nagata, Daisuke
A 79-year-old male chronic hemodialysis patient with no history of central venous catheterization was referred to our hospital with progressive swelling of the left upper limb ipsilateral to a forearm arteriovenous fistula. Radiological assessments revealed marked hyperostosis in the ribs, sternum, and clavicles with well-developed ossification of the sternocostoclavicular ligaments. Such characteristic structural abnormalities and our failure to identify the left subclavian vein with contrast material despite the abundant dilated collaterals in the left shoulder area encouraged us to diagnose our patient with sternocostoclavicular hyperostosis (SCCH) complicated by central vein obstruction. The structural impact of the sternocostoclavicular region as a potential risk for inducing central vein obstruction and the diagnostic concerns of SCCH in this patient are also discussed.